2020
DOI: 10.1177/0957650920910597
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation into the mechanism regarding the inception and evolution of flow unsteadiness induced by the tip leakage flow in a transonic compressor

Abstract: Unsteady flow in the blade tip region of modern axial flow compressors is one of the sources of loss, noise, and blade vibration. In some cases, it is potentially linked to stall inception. In this paper, the complex flow fields in the blade tip region of a transonic axial flow compressor rotor have been numerically investigated. The predicted results were validated by experimental data. Analyses of monitoring results of numerical probes showed that three typical flow characteristics occurred as the operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…It is showed that the total pressure ratio was generally lower than the test results, which might be explained by the difference in data processing between the experimental and numerical methods, and was consistent with the comparisons of other researchers. 22 On the whole, the overall trend of the curves obtained by numerical calculation is in good agreement with the experimental dates. Figure 5 further shows the comparison between the numerical and experimental radial distribution of the total pressure ratio and total temperature ratio at the compressor outlet at the peak efficiency point (PEP) and near stall point (NSP).…”
Section: Transonic Axial-flow Compressor and Numerical Methodssupporting
confidence: 72%
“…It is showed that the total pressure ratio was generally lower than the test results, which might be explained by the difference in data processing between the experimental and numerical methods, and was consistent with the comparisons of other researchers. 22 On the whole, the overall trend of the curves obtained by numerical calculation is in good agreement with the experimental dates. Figure 5 further shows the comparison between the numerical and experimental radial distribution of the total pressure ratio and total temperature ratio at the compressor outlet at the peak efficiency point (PEP) and near stall point (NSP).…”
Section: Transonic Axial-flow Compressor and Numerical Methodssupporting
confidence: 72%
“…This assumption is also widely used in air/ refrigerant compressors and expanders. 15,25 The flow field obeys mass conservation equation and momentum conservation equation. In addition, the air velocity is high and the pressure difference between the inlet boundary and outlet boundary is large, then, the density of the air significantly changes when the air passes through the gap, therefore, the energy conservation equation should be considered.…”
Section: Numerical Simulation Model For Calculating the Circumferenti...mentioning
confidence: 99%
“…Soderquist et al 13 explained the connections between the variations in circumferential rotor power and the inlet total pressure distortion, pressure-induced swirl, total pressure distortion transfer, and total temperature distortion production. An et al 14 used numerical analysis to examine the complicated flow fields in a transonic axial flow compressor rotor's blade tip area, and the characteristic frequency and amplitude of the flow oscillation showed a significant shift with the modification of the vortex breakdown shape.…”
Section: Introductionmentioning
confidence: 99%